Intermediality, Intertextuality, and Remediation: A Literary Perspective on Intermediality - Rajewsky, Irina (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2005)
The concept of intermediality has come to be part of a fixed critical inventory in the debate on literature and the other arts and media. Although there is relative agreement with respect to a definition of intermediality in a broad sense, the research spectrum becomes much more complex, and often contradictory, when precise formal distinctions and the specification and definition of any one particular concept of intermediality are needed. Based on the current state of the question, the present essay specifies one particular approach to intermediality, introducing three more narrowly conceived subcategories, medial transposition, media combination, and intermedial references. By comparison with the genealogical “remediation” concept of Bolter and Grusin, it is shown with respect to which objects and specific research objectives this subdivided concept gains heuristic and practical value. This is particularly the case when detailed analyses of specific medial configurations, their respective meaning-constitutional strategies, and their overall signification are considered.